2008
DOI: 10.1111/j.1540-627x.2008.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Cultural Comparison of the Plural Forms in Franchise Networks: United States, France, and Brazil

Abstract: This paper explores the phenomenon of plural forms (i.e., the simultaneous coexistence of franchised and company-owned outlets, operationally, the proportion of company-owned units in franchise systems based on literature, in franchising across three countries from three continents, namely the United States, France, and Brazil in what is ostensibly the first cross-cultural comparison of its kind. Based on 2003 secondary data, we carry out a series of inferentially grounded analyses involving the plural forms p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
99
0
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(116 citation statements)
references
References 42 publications
(97 reference statements)
9
99
0
8
Order By: Relevance
“…(and prefer) the appointment of expatriates who are "tried and true" principals or trusted agents' (Brock et al, 2008(Brock et al, , p. 1297. In addition, Brazilian firms operate in a high collectivist culture (Beekun, Stedham, & Yamamura, 2003) typically adopting a person-centred approach management style, and valuing non-monetary social goals over financial performance (Dant, Perrigot, & Cliquet, 2008;Nicholls-Nixon et al, 2011). Rodrigues and Betania (2002) reported that Brazilian employees feel out of their comfort zone in formal settings and often try to create a climate of personal intimacy and cordiality in business settings (Amado & Brasil, 1991).…”
Section: Drivers Of Standardisationmentioning
confidence: 99%
“…(and prefer) the appointment of expatriates who are "tried and true" principals or trusted agents' (Brock et al, 2008(Brock et al, , p. 1297. In addition, Brazilian firms operate in a high collectivist culture (Beekun, Stedham, & Yamamura, 2003) typically adopting a person-centred approach management style, and valuing non-monetary social goals over financial performance (Dant, Perrigot, & Cliquet, 2008;Nicholls-Nixon et al, 2011). Rodrigues and Betania (2002) reported that Brazilian employees feel out of their comfort zone in formal settings and often try to create a climate of personal intimacy and cordiality in business settings (Amado & Brasil, 1991).…”
Section: Drivers Of Standardisationmentioning
confidence: 99%
“…Após tal estudo, pesquisas identificaram a coexistência de mais de uma forma de governança na mesma cadeia produtiva para coordenar transações similares (BRADACH, 1997;MOLS, 2000;AFFUSO, 2002;ZYLBERSZTAJN e NOGUEIRA, 2002;HEIDE, 2003;PARMIGIANI, 2007; SILVA e AZEVEDO, 2007;DANT et al, 2008;MONDELLI e ZYLBERSZTAJN, 2008;GELLYNCK e MOLNÁR, 2009;MELLO e PAULILLO, 2010;LEME e ZYLBERSZTAJN, 2012;BROKES e ROPER, 2012;MENARD, 2013). Cabe, neste contexto, observar que o estudo de Monteiro et al (2012) apresenta um interessante quadro das pesquisas empíricas que buscam entender as formas complexas de governança no sistema agroindustrial brasileiro.…”
Section: Formas Plurais De Governançaunclassified
“…A principal vantagem ao se utilizar esses anuários reside na disponibilidade de dados sobre muitas redes de franquias. Essas produções científicas datam do início dos anos 90 até os presentes anos (Castrogiovanni & Justis, 2002;Combs & Castrogiovanni, 1994;Dant, Perrigot, & Cliquet, 2008;Elango, 2007;Mariz-Pérez & García-Álvarez, 2009 A variável independente dos modelos é o fato da franquia ser uma microfranquia (investimento menor que R$ 50 mil) ou franquia convencional. Tal variável constitui uma dummy em que 1 é a microfranquia e 0, a franquia convencional.…”
Section: Metodologia Descrição Do Método E Procedimentosunclassified